Gratitude as a Buffer: Exploring Its Moderating Role in the Link Between Daily Hassles and Life Satisfaction Among Students - Nugraha, Dibyo Restu; Nugraha, Dwi Yan; Jamaluddin, Bambang Pratama; Imam, Andi Khaerul; Mubharak, Fadhil (Al-Qalb : Jurnal Psikologi Islam, 2024)
Satisfaction with life is part of the cognitive process that can be negatively affected by perceptions of everyday events, which is known as daily hassles. A sense of gratitude is always appreciating, recognizing, and responding to life events that are determinants of mental health and well-being, and have been shown to increase satisfaction with life. The purpose of this study is to investigate the moderating role of gratitude in the relationship between daily hassles and satisfaction with life. The study used a quantitative approach with a cross-sectional design and involved 169 undergraduate students as respondents. The selected respondents will fill out three research scales, namely the lives daily hassles scale (LIVES-DHS) 18 items, the gratitude questionnaire – five item form (GQ-5), and the satisfaction with life scale (SWLS) 5 items. Moderated regression analysis was conducted to test the role of gratitude as a moderator using R programming language (v4.4.0) and RStudio (v2024.04.1-748). Our results show that gratitude acts as a moderator in the relationship between daily hassles and satisfaction with life. This study contributes as a reference material in implementing gratitude interventions to increase satisfaction with life in dealing with daily hassles